2018
DOI: 10.17221/96/2018-pse
|View full text |Cite
|
Sign up to set email alerts
|

Wheat straw mulching with fertilizer nitrogen: An approach for improving soil water storage and maize crop productivity

Abstract: Field studies using wheat straw mulching effects on soil water storage and maize development were conducted in China. The studies contained four treatments during three years (2014–2016): CK (no straw and no nitrogen); N (no straw mulching with 172 kg N/ha); HS + N (half straw mulching at the rate of 2500 kg/ha with 172 kg N/ha), and FS + N (full straw mulching at the rate of 5000 kg/ha with 172 kg N/ha). The FS + N treatment significantly increased soil water storage in a drought period during crop growth sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Second, the addition of the decomposer might have offset some negative effects caused by the initial straw and soil chemical composition and the unfavorable soil moisture and temperature conditions during the early stages of straw decomposition through the multilateral reaction among them, synergistically enhancing the buried straw decomposition and C and N release, which was similar to the finding in the maize straw incubation reported by Qin et al (2015). Finally, the released straw C and N were slowly converted into soil carbon and nitrogen that reduced the native SOC and SON lost via crop uptake, increasing soil carbon and nitrogen accumulation and storage (Akhtar et al 2018).…”
Section: Relationship Correlating Straw Decomposition and Straw C Andsupporting
confidence: 82%
See 2 more Smart Citations
“…Second, the addition of the decomposer might have offset some negative effects caused by the initial straw and soil chemical composition and the unfavorable soil moisture and temperature conditions during the early stages of straw decomposition through the multilateral reaction among them, synergistically enhancing the buried straw decomposition and C and N release, which was similar to the finding in the maize straw incubation reported by Qin et al (2015). Finally, the released straw C and N were slowly converted into soil carbon and nitrogen that reduced the native SOC and SON lost via crop uptake, increasing soil carbon and nitrogen accumulation and storage (Akhtar et al 2018).…”
Section: Relationship Correlating Straw Decomposition and Straw C Andsupporting
confidence: 82%
“…This showed that adding decomposer with FM tillage also was the most favorable technique for straw C and N degradation and release. This contributed to the synergistic effects of enhanced soil microbial activity and modified soil hydrothermal conditions (Zhao et al 2017;Akhtar et al 2018). Also, the results indicate that a fast release of straw C and N lasted for 210 days of incubation in the presence of the straw decomposer, but it was longer than that found by Wang (2015) and Ali Abro et al (2011), mainly because of the difference in the incubation period and the aerobic conditions.…”
Section: Straw Decomposition and Straw C And N Release As Affected Bymentioning
confidence: 62%
See 1 more Smart Citation
“…Agricultural sustainability is defined as the ability of a crop production system to continuously produce food without environmental degradation (Pan et al., 2021; Pang et al., 2020). The use of rice straw and different tillage practices are considered eco‐friendly strategies for sustainable agriculture crop production (Kashif et al., 2018). Sustainable crop production, especially rice farming under a dual cropping system in south China is thought to be achievable by effective conservation management practices.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in fruit yield was especially observed in the application of DSM and PM of 120 cm soil depth. It could be due to the various effects of mulch on plant growth periods such as protection of surface soil structure and rainwater, improving soil physical and chemical properties, and increasing water storage capacity (Kashif et al, 2018).…”
Section: Measured Charactersmentioning
confidence: 99%